(untitled) (Studia Prawnicze / The Legal Studies, 1963)
The contribution of land to productive agricultural cooperatives has two aspects from a social and economic point of view: on the one hand, it results in the consolidation of small, often poorly developed peasant farms into larger economic entities, which allows for the mechanisation of work and ensures management with professional knowledge. On the other hand, this leads to the socialisation of the means of production in agriculture, which, like the socialisation of industry, is an indispensable condition for building the economic basis of society. In accordance with the law of 17 February 1961, art. 97 on cooperatives and their associations, the land may be contributed to the cooperative not only by the owner, but also by the possessor, if the latter is a a possessor by right of ownership and in good faith. However, the contribution of land by an unauthorised person is valid in the sense that the land can become the object of contribution. This does not infringe on the owner’s benefits resulting from the legal relationship (e.g. lease) between him and the person who brought the land to the cooperative without the owner’s permission. In addition, the owner can support his claim for damages against the cooperative. In principle, members must contribute all the land they own to the cooperative. However, considering that our productive agricultural cooperatives are still in the preliminary phase of development, the law allows for the establishment of cooperatives of a sort of experimental character, where the turnover of all the land owned is not mandatory. In addition, the statutes of each cooperative may provide for the possibility of reserving to members the right to retain part of the land owned for their own economic needs. From the moment the land is contributed to the cooperative, the cooperative acquires the right to use it. However, this usufruct differs in many respects from a usufruct standardised by civil law. The most important deviation is that, according to the provisions of the statute, the cooperative may have the right to change the intended purpose of the land, as well as the alteration of the substance of the used land. This usufruct is indefinite as, in principle, it lasts as long as the cooperative, but may be extinguished earlier by the withdrawal of the territorial contribution made by the cooperative member at the time. Despite the contribution of the land to the cooperative, it belongs to the owner, i.e. the member of the cooperative or to a third person, where the land was brought in by the possessor. The consequence of this principle is that the owner can freely dispose of his property, in case of his death or by deeds between living persons. If the third persons have rights to the land contributed to the cooperative, apart from property rights, the fate of these rights is subject to certain deviations from the general principles concerning the effectiveness of real rights, as well as relative rights. This means, in principle, that real rights last, despite the contribution of the land to the cooperative, whereas relative rights are extinguished if the law does not provide for an exception (e.g. as a lease). The owner of the land contributed to the cooperative can claim it at the appropriate time. This principle remains in force without restrictions, if the owner of the land is a third person or the legal successor of the member and especially his successor. On the other hand, if the land belongs to the cooperative member, the latter has the right to it only when he ceases to be a member of the cooperative, which, among other things, happens after the member has given notice. The owner-member, when withdrawing his contribution to the cooperative, receives, in principle, the same land he contributed, if this does not hinder the economic needs of the complex (e.g. if the cooperative has built a building on the said land). In this particular case, the owner has the right to an exchangeable parcel with consideration of mutual interests. This exchange can take place when the interested persons: the owner of the withdrawn land, the owner of the land to which the exchangeable parcel is to be extracted, and the cooperative in question, give their assent, by entering into a contract. In the event of a dispute concerning the delivery of the exchangeable plot, the administrative bodies decide. For, in a case of exchange, it is not only a civil dispute, but, above all, an exchange of land which would have as its aim the improvement of the agricultural structure in the region which, as such, does not depend on jurisprudence, but on administrative bodies.